Neural correlates of head restraint: Unsolicited neuronal activation and dopamine release - Tomoo Inubushi; Masanori Ito; Yutaro Mori; Masami Futatsubashi; Kengo Sato; Shigeru Ito; Masamichi Yokokura; Tomomi Shinke; Yosuke Kameno; Akihiro Kakimoto; Toshihiko Kanno; Hiroyuki Okada; et al. (NeuroImage, 2021)
To minimize motion-related distortion of reconstructed images, conventional positron emission tomography (PET) measurements of the brain inevitably require a firm and tight head restraint. While such a restraint is now a routine procedure in brain imaging, the physiological and psychological consequences resulting from the restraint have not been elucidated. To address this problem, we developed a restraint-free brain PET system and conducted PET scans under both restrained and non-restrained conditions. We examined whether head restraint during PET scans could alter brain activities such as regional cerebral blood flow (rCBF) and dopamine release along with psychological stress related to head restraint. Under both conditions, 20 healthy male participants underwent [15O]H2O and [11C]Raclopride PET scans during working memory tasks with the same PET system. Before, during, and after each PET scan, we measured physiological and psychological stress responses, including the State-Trait Anxiety Inventory (STAI) scores. Analysis of the [15O]H2O-PET data revealed higher rCBF in regions such as the parahippocampus in the restrained condition. We found the binding potential (BPND) of [11C]Raclopride in the putamen was significantly reduced in the restrained condition, which reflects an increase in dopamine release. Moreover, the restraint-induced change in BPND was correlated with a shift in the state anxiety score of the STAI, indicating that less anxiety accompanied smaller dopamine release. These results suggest that the stress from head restraint could cause unsolicited responses in brain physiology and emotional states. The restraint-free imaging system may thus be a key enabling technology for the natural depiction of the mind.